2003
DOI: 10.1093/emboj/cdg218
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of preadipocyte differentiation by steroid through targeting of an HDAC1 complex

Abstract: Glucocorticoids potentiate the early steps of preadipocyte differentiation and promote obesity in Cushing's syndrome and during prolonged steroid therapy. We show that glucocorticoids stimulate 3T3 L1 preadipocyte differentiation through a non-transcriptional mechanism mediated through the ligand-binding domain of the glucocorticoid receptor. This enhanced the onset of CCAAT/enhancer binding protein (C/EBPa) expression by potentiating its initial transcriptional activation by C/EBPb. In the absence of steroid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 61 publications
10
150
2
Order By: Relevance
“…HDACs are enzymes that play an important role in the regulation of gene expression and are best known for their role in repressing gene transcription via interaction with transcriptional repressors [Ng and Bird, 2000]. Interestingly, both HDACs and transcriptional repressors have previously been implicated in the regulation of adipocyte differentiation: HDAC-1 has been shown to associate with the C/EBPa promoter and play an important role in preventing C/EBPa expression in unstimulated preadipocytes [Wiper-Bergeron et al, 2003], while a number of transcriptional repressors have been implicated in the regulation of adipogenesis via the direct inhibition of both C/EBPa and PPARg gene expression [Tong et al, 2000;Yun et al, 2002;Banerjee et al, 2003;Shi et al, 2003]. Hence, it is tempting to speculate that one potential mechanism by which the PGF2a-calcineurin signaling pathway may inhibit adipocyte differentiation is by inducing the expression and/or activity of an HDAC-associated transcriptional repressor that is either able to directly inhibit the expression of the PPARg and C/EBPa genes, or alternatively, acts indirectly, by inhibiting the expression of a gene(s) that is normally required to promote the expression of PPARg and C/ EBPa.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs are enzymes that play an important role in the regulation of gene expression and are best known for their role in repressing gene transcription via interaction with transcriptional repressors [Ng and Bird, 2000]. Interestingly, both HDACs and transcriptional repressors have previously been implicated in the regulation of adipocyte differentiation: HDAC-1 has been shown to associate with the C/EBPa promoter and play an important role in preventing C/EBPa expression in unstimulated preadipocytes [Wiper-Bergeron et al, 2003], while a number of transcriptional repressors have been implicated in the regulation of adipogenesis via the direct inhibition of both C/EBPa and PPARg gene expression [Tong et al, 2000;Yun et al, 2002;Banerjee et al, 2003;Shi et al, 2003]. Hence, it is tempting to speculate that one potential mechanism by which the PGF2a-calcineurin signaling pathway may inhibit adipocyte differentiation is by inducing the expression and/or activity of an HDAC-associated transcriptional repressor that is either able to directly inhibit the expression of the PPARg and C/EBPa genes, or alternatively, acts indirectly, by inhibiting the expression of a gene(s) that is normally required to promote the expression of PPARg and C/ EBPa.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone treatment also inhibited the activity of adipose tissue LPL (21,22). On the other hand, the specific role of progesterone on fat metabolism is not yet completely elucidated, as some studies found that progesterone stimulated fat accumulation, LPL activity, lipogenesis, and steroid-mediated differentiation of preadipocytes (20,32,35), and others reported that progesterone could be responsible for the female fat distribution pattern via an anti-glucocorticoid action in abdominal fat (26,37). Whether increased metabolism of these steroids in adipose tissue of obese women, through enzymes examined here, relates to actually increased or reduced binding of the steroids to their receptors remains unclear (16).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, GCs can enhance the function of C/EBPβ. This process involves the phosphorylation of C/EBPβ and exchange of associated coactivator/corepressor proteins, although it is unclear whether a direct interaction between GR and C/EBPβ is required (Berg et al, 2005;Boruk et al, 1998;Wiper-Bergeron et al, 2003).…”
Section: A Clarkmentioning
confidence: 99%